Hot-rolled steel material

By adding Cu, Sb, Ni, In to the steel, and controlling its content and hot rolling conditions, the Cu and In enrichment areas in the oxide layer are formed, which solves the problem of insufficient corrosion resistance of existing steels in sulfuric acid humidity corrosion environments, and improves the hot processing performance and achieves excellent corrosion performance in high reactivity and low concentration sulfuric acid environments.

JP2025042920APending Publication Date: 2025-03-28NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023150122
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the sulfuric acid humidity corrosion environment, especially in the low-concentration sulfuric acid environment, the corrosion resistance of existing steels is insufficient, and the thermal processing performance is not good under high-temperature working conditions.

Method used

Hot-rolled steel containing elements such as Cu, Sb, Ni, In, and other elements are used, and Cu and In enrichment areas in the oxide layer are formed by controlling the Cu and In content and hot rolling conditions, corrosion resistance to low-concentration sulfuric acid is improved while maintaining good hot processing performance.

Benefits of technology

The corrosion resistance of steel in sulfuric acid humidity corrosion environment is significantly improved, including a high-reactive sulfuric acid humidity corrosion environment and a low-concentration sulfuric acid environment, while maintaining good thermal processing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042920000001
    Figure 2025042920000001
  • Figure 2025042920000002
    Figure 2025042920000002
  • Figure 2025042920000003
    Figure 2025042920000003
Patent Text Reader

Abstract

To provide a hot-rolled steel material having excellent corrosion resistance in a sulfuric acid dew point corrosion environment and a mildly acidic sulfuric acid environment and excellent hot workability.SOLUTION: Provided is a hot-rolled steel material having oxide scale on at least a part of the surface of a base metal. The chemical composition of the base metal, in mass%, is C: 0.01-0.10%, Si: 0.04-0.40%, Mn: 0.50-1.50%, Cu: 0.10-0.50%, Sb: 0.01-0.30%, Ni: 0.02-0.30%, In: 0.005-0.020%, Al: 0.005-0.05%, the sum of one or both Mo and W: 0.01-0.30%, P: 0.015% or less, S: 0.015% or less, N: 0.005% or less, O: 0.0035% or less, and the balance: Fe and impurities, satisfying 10.0≤Cu / In and 2.6≤(Cu / 64) / ((Sb / 122)+(In / 115))≤5.5, and having Cu and In enrichments in the oxide scale.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot rolled steel material. [Background technology]

[0002] Boiler furnaces and incinerators at waste incineration facilities generate exhaust gases that contain water vapor, sulfur oxides, hydrogen chloride, etc. When this exhaust gas is cooled in the exhaust gas chimney, etc., it condenses into sulfuric acid, which causes severe corrosion of the steel materials that make up the exhaust gas passage, a phenomenon known as sulfuric acid dew-point corrosion.

[0003] To address these problems, sulfuric acid dew-point corrosion resistant steels and highly corrosion resistant stainless steels have been proposed. For example, Patent Documents 1 to 5 propose steel materials with excellent sulfuric acid dew-point corrosion resistance to which Cu, Sb, Co, Cr, etc. have been added. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-164335 A [Patent Document 2] JP 2003-213367 A [Patent Document 3] JP 2007-239094 A [Patent Document 4] JP 2012-57221 A [Patent Document 5] International Publication No. 2021 / 095185 Summary of the Invention [Problem to be solved by the invention]

[0005] In a sulfuric acid dew-point corrosion environment such as an exhaust gas chimney, when the temperature of the exhaust gas drops, the water vapor in the exhaust gas first condenses on the surface of the steel material, where sulfur oxides dissolve. The high-concentration sulfuric acid thus produced is highly reactive. Steel materials containing Cu, Sb, Cr, etc. have excellent corrosion resistance in such a sulfuric acid dew-point corrosion environment.

[0006] On the other hand, in an environment of about 40°C where the amount of condensed water further increases, low-concentration sulfuric acid with a pH of about 2 to 3 is generated. When the temperature of exhaust gas fluctuates in the environment in which the steel is used, or when part of the steel is exposed to high-temperature exhaust gas and other parts are exposed to low-temperature exhaust gas, the steel is exposed to both a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment. Therefore, it is required to exhibit good corrosion resistance in both a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment. However, although conventional steels have excellent corrosion resistance in a sulfuric acid dew-point corrosion environment, there is still room for improvement in corrosion resistance in a weakly acidic sulfuric acid environment.

[0007] Furthermore, when used for incinerator flues in gasification melting furnaces, heat exchangers, gas-gas heaters, desulfurization equipment, electric dust collectors, and the like in addition to exhaust gas chimneys, not only corrosion resistance but also hot workability is required from the standpoint of workability and productivity.

[0008] An object of the present invention is to solve the above problems and to provide a steel material having excellent corrosion resistance in a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment, and also excellent hot workability. [Means for solving the problem]

[0009] The present invention has been made to solve the above problems, and the gist of the present invention is the following steel material.

[0010] (1) A hot-rolled steel material having an oxide scale on at least a portion of a surface of a base material, The chemical composition of the base material is, in mass%, C: 0.01 to 0.10%, Si: 0.04 to 0.40%, Mn: 0.50-1.50%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Ni: 0.02 to 0.30%, In: 0.005~0.020%, Al: 0.005 to 0.05%, Sum of Mo and / or W: 0.01 to 0.30%, P: 0.015% or less, S: 0.015% or less, N: 0.005% or less, O: 0.0035% or less, The balance is Fe and impurities. The following formulas (i) and (ii) are satisfied: The oxide scale has a Cu and In enriched portion. Hot rolled steel. 10.0≦Cu / In (i) 2.6≦(Cu / 64) / ((Sb / 122)+(In / 115))≦5.5 (ii) In the above formula, the element symbols represent the content (mass%) of each element contained in the hot-rolled steel material.

[0011] (2) A hot-rolled steel material having an oxide scale on at least a part of a surface of a base material, The chemical composition of the base material is, in mass%, C: 0.01 to 0.10%, Si: 0.04 to 0.40%, Mn: 0.50-1.50%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Ni: 0.02 to 0.30%, In: 0.005~0.020%, Al: 0.005 to 0.05%, Sum of Mo and / or W: 0.01 to 0.30%, P: 0.015% or less, S: 0.015% or less, N: 0.005% or less, O: 0.0035% or less, and further containing one or more selected from the group consisting of the following groups A, B, and C: The balance is Fe and impurities. The following formulas (i) and (ii) are satisfied: The oxide scale has a Cu and In enriched portion. Hot rolled steel. 10.0≦Cu / In (i) 2.6≦(Cu / 64) / ((Sb / 122)+(In / 115))≦5.5 (ii) In the above formula, the element symbols represent the content (mass%) of each element contained in the hot-rolled steel material. [Group A] One or more selected from the group consisting of As: 0.10% or less, Bi: 0.10% or less, Se: 0.10% or less, Te: 0.10% or less, Pb: 0.10% or less, Zn: 0.10% or less, Ga: 0.10% or less, Ge: 0.10% or less, Co: 0.30% or less, and Hf: 0.30% or less. [Group B] One or more selected from the group consisting of Cr: 1.0% or less, Nb: 0.10% or less, V: 0.10% or less, Ti: 0.20% or less, Zr: 0.20% or less, Ta: 0.05% or less, and B: 0.010% or less [Group C] One or more selected from the group consisting of Ca and Mg, one or both of which in total are 0.010% or less, Sr and Ba, one or both of which in total are 0.010% or less, and REM, which are 0.010% or less

[0012] (3) The hot-rolled steel material according to (2) above, wherein the chemical composition of the base material contains one or more elements selected from Group A.

[0013] (4) The hot-rolled steel material according to (2) above, wherein the chemical composition of the base material contains one or more elements selected from the B group.

[0014] (5) The hot-rolled steel material according to (2) above, wherein the chemical composition of the base material contains one or more elements selected from the C group. Effect of the Invention

[0015] According to the present invention, it is possible to obtain a hot-rolled steel material having excellent corrosion resistance in a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment, and also excellent hot workability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In order to achieve the above object, the present inventors have conducted detailed investigations into the corrosion resistance and hot workability of steel materials, and have come to the following findings.

[0017] The inclusion of Cu, Sb, etc. in steel improves the acid corrosion resistance to sulfuric acid. However, as a result of further investigation by the present inventors, it was found that there is room for improvement in order to improve the corrosion resistance to highly reactive low-concentration sulfuric acid.

[0018] As a result of detailed investigations, the present inventors first found that Cu-enriched parts exist in the oxide scale formed on the surface of the steel material. They also found that by strictly adjusting the contents of Cu and In and simultaneously adding them and appropriately controlling the hot rolling conditions, it is possible to enrich In in the Cu-enriched parts in the oxide scale. They also found that by forming Cu- and In-enriched parts in the oxide scale, a barrier effect against low-concentration sulfuric acid is exerted, and the corrosion resistance against low-concentration sulfuric acid can be improved.

[0019] The detailed mechanism by which Cu and In concentrate in the oxide scale to improve corrosion resistance against low-concentration sulfuric acid is unknown. However, the following mechanism is presumed. In is an element that easily diffuses in oxide scale, and in the absence of Cu, it diffuses to the outermost layer of the oxide scale. In addition, since In is a low-melting-point metal, it becomes liquid in the outermost layer of the oxide scale. As a result, the adhesion of the outermost layer of the oxide scale deteriorates, and the outermost layer of the oxide scale peels off together with the liquid In. Therefore, it is unable to exert a barrier effect against low-concentration sulfuric acid.

[0020] On the other hand, if the oxide scale contains Cu, it is likely that Cu will easily form compounds with In, and this will suppress the diffusion of In in the oxide scale. Furthermore, since In has low solubility in a weakly acidic environment with a pH of 2 to 3, it is presumed that this acts as a barrier against low-concentration sulfuric acid.

[0021] However, while Cu, Sb, and In improve the corrosion resistance in a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment, they also reduce the hot workability. In particular, when Cu, Sb, and In coexist, they further reduce the hot workability. As a result, the hot workability is significantly reduced. Therefore, by controlling the Sb and In contents relative to the Cu content, it is possible to achieve both excellent corrosion resistance in a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment and excellent hot workability.

[0022] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.

[0023] (A) Chemical composition of the base material The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0024] C: 0.01 to 0.10% C is an element that improves the strength of steel. However, if C is contained in excess, it deteriorates the weld heat affected zone. Therefore, the C content is set to 0.01 to 0.10%. The C content is preferably 0.03% or more, and more preferably 0.05% or more. Moreover, the C content is preferably 0.08% or less, and more preferably 0.06% or less.

[0025] Silicon: 0.04 to 0.40% Silicon is an element that contributes to improving deoxidation and strength, and controls the morphology of oxides. However, when excessive silicon is contained, it reduces toughness. Therefore, the silicon content is set to 0.04 to 0.40%. The silicon content is preferably 0.10% or more, and more preferably 0.15% or more. The silicon content is preferably 0.35% or less, and more preferably 0.30% or less.

[0026] Mn: 0.50 to 1.50% Mn is an element that improves strength and toughness. However, if Mn is contained in excess, mechanical properties deteriorate. Therefore, the Mn content is set to 0.50 to 1.50%. The Mn content is preferably 0.70% or more, and more preferably 0.90% or more. In addition, the Mn content is preferably 1.40% or less, more preferably 1.30% or less, and even more preferably 1.20% or less.

[0027] Cu: 0.10-0.50% Cu is an element that, when contained simultaneously with Sb, significantly exhibits corrosion resistance against sulfuric acid. However, when Cu is contained in excess, hot workability is reduced, impairing productivity. Therefore, the Cu content is set to 0.10 to 0.50%. The Cu content is preferably 0.15% or more, more preferably 0.20% or more, and even more preferably 0.25% or more. Moreover, the Cu content is preferably 0.45% or less, and more preferably 0.40% or less.

[0028] Sb: 0.01 to 0.30% Sb is an element that, when contained simultaneously with Cu, significantly exhibits corrosion resistance against sulfuric acid. However, when Sb is contained in excess, hot workability is reduced, impairing productivity. Therefore, the Sb content is set to 0.01 to 0.30%. The Sb content is preferably 0.05% or more, more preferably 0.10% or more, and even more preferably 0.15% or more. Moreover, the Sb content is preferably 0.25% or less, and more preferably 0.20% or less.

[0029] Ni: 0.02 to 0.30% Ni is an element that improves corrosion resistance in an acid corrosion environment, and also has the effect of improving manufacturability in steel containing Cu. Cu has a large effect of improving corrosion resistance, but it is easily segregated, and if it is contained alone, it may promote cracking after casting. On the other hand, Ni has the effect of reducing the surface segregation of Cu. By containing Ni, in addition to suppressing Cu segregation and cast cracking, the occurrence of local corrosion due to segregation is also suppressed, so that the effect of improving corrosion resistance is obtained. However, Ni is an expensive element, and the inclusion of a large amount leads to an increase in steelmaking costs. Therefore, the Ni content is set to 0.02 to 0.30%. The Ni content is preferably 0.05% or more, more preferably 0.08% or more, and even more preferably 0.10% or more. Moreover, the Ni content is preferably 0.25% or less, more preferably 0.20% or less.

[0030] In: 0.005 to 0.020% In is an element that improves corrosion resistance in a weakly acidic sulfuric acid environment. However, if In is contained in excess, hot workability decreases. Therefore, the In content is set to 0.005 to 0.020%. The In content is preferably 0.008% or more, and more preferably 0.010% or more. Moreover, the In content is preferably 0.018% or less, and more preferably 0.015% or less.

[0031] Al: 0.005 to 0.05% Al is added as a deoxidizer. However, if an excessive amount of Al is contained, it deteriorates the toughness of the weld metal part. Therefore, the Al content is set to 0.005 to 0.05%. The Al content is preferably 0.01% or more, and more preferably 0.02% or more. Moreover, the Al content is preferably 0.04% or less, and more preferably 0.03% or less.

[0032] Sum of Mo and / or W: 0.01 to 0.30% Mo and W are elements that improve corrosion resistance in an acid corrosion environment when contained simultaneously with Cu and Sb. However, since Mo and W are expensive elements, excessive inclusion leads to a decrease in economic efficiency. Therefore, the total content of Mo and W is set to 0.01 to 0.30%. Mo and W may be contained alone or both may be contained simultaneously. The total content of Mo and W is preferably 0.05% or more, more preferably 0.10% or more. Moreover, the total content of Mo and W is preferably 0.25% or less, more preferably 0.20% or less.

[0033] P:0.015% or less P is an impurity that reduces the mechanical properties and productivity of steel. Therefore, the upper limit of the P content is set to 0.015% or less. The P content is preferably 0.013% or less, and more preferably 0.010% or less. It is preferable to reduce the P content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the P content may be 0.001% or more, or 0.003% or more.

[0034] S: 0.015% or less S is an impurity that reduces the mechanical properties and productivity of steel materials. Therefore, the upper limit of the S content is set to 0.015% or less. The S content is preferably 0.013% or less, and more preferably 0.010% or less. It is preferable to reduce the S content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the S content may be 0.001% or more, or 0.003% or more.

[0035] N: 0.005% or less N is an impurity that reduces the mechanical properties and productivity of steel. Therefore, the upper limit of the N content is set to 0.005% or less. The N content is preferably 0.004% or less, and more preferably 0.003% or less. The N content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the N content may be 0.001% or more. Furthermore, N has the effect of contributing to the improvement of mechanical properties, etc. by precipitating as fine nitrides. If this effect is desired, the N content may be 0.002% or more.

[0036] O: 0.0035% or less O is an impurity that forms coarse oxides that become the starting point of corrosion in an acid corrosion environment. Therefore, the upper limit of the O content is set to 0.0035% or less. The O content is preferably 0.0030% or less, and more preferably 0.0025% or less. It is preferable to reduce the O content as much as possible, that is, the content may be 0%, but an extreme reduction leads to an increase in steelmaking costs. Therefore, the O content may be 0.0005% or more, or 0.0010% or more.

[0037] In the chemical composition of the steel material of the present invention, the balance is Fe and impurities. Here, the impurities refer to components that are mixed in due to raw materials such as ores and scraps or other factors during industrial production of the steel material, and are permissible within a range that does not adversely affect the steel material of the present invention.

[0038] 10.0≦Cu / In (i) As described above, it is necessary to strictly adjust the contents of Cu and In. Specifically, if the Cu content is too low relative to the In content, In cannot form a compound with Cu, and In cannot concentrate in the oxide scale. Therefore, it is necessary to satisfy formula (i). The element symbols in formula (i) above represent the contents (mass%) of each element contained in the hot-rolled steel material. The value on the right side of formula (i) is preferably 15.0 or more, and more preferably 20.0 or more.

[0039] The upper limit of the right-hand side of formula (i) is not particularly limited. However, if the Cu content is excessive relative to the In content, the effect is saturated and the hot workability due to the coexistence of Cu and In may be significantly reduced, so the right-hand side of formula (i) is preferably 75.0 or less. The right-hand side of formula (i) is more preferably 70.0 or less.

[0040] 2.6≦(Cu / 64) / ((Sb / 122)+(In / 115))≦5.5 (ii) As described above, it is necessary to control the Sb and In contents relative to the Cu content. If the Sb and In contents are excessive relative to the Cu content, the hot workability deteriorates. On the other hand, if the Sb and In contents are too small relative to the Cu content, it is not possible to ensure corrosion resistance in a sulfuric acid dew-point corrosion environment and a weakly acidic sulfuric acid environment. Therefore, it is necessary to satisfy formula (ii). The element symbols in formula (ii) above represent the contents (mass%) of each element contained in the hot-rolled steel material.

[0041] Formula (ii) is composed of the numbers of Cu, Sb, and In atoms. That is, Cu / 64, Sb / 122, and In / 115 are terms obtained by dividing the contents of Cu, Sb, and In by the mass numbers of each element, respectively. The value in formula (ii) is preferably 2.8 or more, and more preferably 3.0 or more. Also, the value in formula (ii) is preferably 5.3 or less, and more preferably 5.0 or less.

[0042] In the chemical composition of the steel material of the present invention, one or more elements selected from As, Bi, Se, Te, Pb, Zn, Ga, Ge, Co, and Hf may be further contained within the ranges shown below in order to improve corrosion resistance in an acid corrosion environment. Note that these elements are not necessarily essential for the steel material, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.

[0043] As: 0.10% or less Although As does not have a significant effect compared to Sb, it is an effective element for improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if As is contained in excess, toughness decreases. Therefore, the As content is set to 0.10% or less. The As content is preferably 0.08% or less, and more preferably 0.05% or less. In order to obtain the above effects more reliably, the As content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.04% or more.

[0044] Bi:0.10% or less Although Bi does not have a significant effect compared to Sb, it is an element that is effective in improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if Bi is contained in excess, toughness decreases. Therefore, the Bi content is set to 0.10% or less. The Bi content is preferably 0.08% or less, and more preferably 0.05% or less. In order to obtain the above effects more reliably, the Bi content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more.

[0045] Se: 0.10% or less Although Se does not have a significant effect compared to Sb, it is an effective element for improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if Se is contained in excess, toughness decreases. Therefore, the Se content is set to 0.10% or less. The Se content is preferably 0.08% or less, and more preferably 0.05% or less. In order to obtain the above effects more reliably, the Se content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more.

[0046] Te: 0.10% or less Te does not have a significant effect compared to Sb, but it is an effective element for improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if Te is contained in excess, toughness decreases. Therefore, the Te content is set to 0.10% or less. The Te content is preferably 0.08% or less, and more preferably 0.05% or less. In order to obtain the above effects more reliably, the Te content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more.

[0047] Pb: 0.10% or less Pb forms sulfides with S and is an element that is effective in improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if Pb is contained in excess, toughness deteriorates. Therefore, the Pb content is set to 0.10% or less. The Pb content is preferably 0.08% or less, and more preferably 0.05% or less. In order to obtain the above effects more reliably, the Pb content is preferably 0.005% or more, and more preferably 0.010% or more.

[0048] Zn: 0.10% or less Ga: 0.10% or less Zn and Ga form sulfides with S and are effective elements for improving corrosion resistance in an acid corrosion environment, so either one or both may be contained as necessary. However, if Zn and Ga are contained in excess, toughness deteriorates. Therefore, the contents of Zn and Ga are each set to 0.10% or less. The contents of Zn and Ga are each preferably set to 0.08% or less, and more preferably set to 0.05% or less. In order to more reliably obtain the above effects, the contents of Zn and Ga are each preferably set to 0.005% or more, and more preferably set to 0.010% or more.

[0049] Ge: 0.10% or less Ge forms sulfides with S and is an element that is effective in improving corrosion resistance in an acid corrosion environment, so it may be contained as necessary. However, if Ge is contained in excess, toughness deteriorates. Therefore, the Ge content is set to 0.10% or less. The Ge content is preferably 0.08% or less, and more preferably 0.05% or less. In order to obtain the above effects more reliably, the Ge content is preferably 0.005% or more, and more preferably 0.010% or more.

[0050] Co:0.30% or less Co is an element that forms an oxide and improves corrosion resistance, so it may be contained as necessary. However, if Co is contained in excess, the economic efficiency decreases. Therefore, the Co content is set to 0.30% or less. The Co content is preferably 0.25% or less, and more preferably 0.20% or less. In order to obtain the above effects more reliably, the Co content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.

[0051] Hf: 0.30% or less Hf is an element that forms an oxide and improves corrosion resistance, so it may be contained as necessary. However, if Hf is contained in excess, the economic efficiency decreases. Therefore, the Hf content is set to 0.30% or less. The Hf content is preferably 0.25% or less, and more preferably 0.20% or less. In order to obtain the above effects more reliably, the Hf content is preferably 0.002% or more, and more preferably 0.005% or more.

[0052] In the chemical composition of the steel material of the present invention, in order to improve mechanical properties, etc., one or more elements selected from Cr, Nb, V, Ti, Zr, Ta, and B may be further contained within the ranges shown below. Note that these elements are not necessarily essential for the steel material, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.

[0053] Cr:1.0% or less Cr is an element that improves hardenability and strength, so it may be contained as necessary. However, if Cr is contained in excess, it may deteriorate weldability and toughness. Therefore, the Cr content is set to 1.0% or less. The Cr content is preferably 0.80% or less, more preferably 0.50% or less, and even more preferably 0.30% or less. In order to obtain the above effects more reliably, the Cr content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.05% or more.

[0054] Nb: 0.10% or less Nb is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if Nb is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the Nb content is set to 0.10% or less. The Nb content is preferably 0.09% or less, more preferably 0.08% or less, and even more preferably 0.07% or less. In order to obtain the above effects more reliably, the Nb content is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more.

[0055] V:0.10% or less V, like Nb, is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if V is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the V content is set to 0.10% or less. The V content is preferably 0.08% or less, more preferably 0.06% or less, and even more preferably 0.04% or less. In order to obtain the above effects more reliably, the V content is preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.005% or more.

[0056] Ti: 0.20% or less Ti is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if Ti is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the Ti content is set to 0.20% or less. The Ti content is preferably set to 0.15% or less. In order to more reliably obtain the above effects, the Ti content is preferably set to 0.001% or more, and more preferably set to 0.005% or more.

[0057] Zr: 0.20% or less Zr, like Ti, is an element that forms nitrides and contributes to refining crystal grains and improving strength, so it may be contained as necessary. However, if Zr is contained in excess, the nitrides become coarse and mechanical properties deteriorate. Therefore, the Zr content is set to 0.20% or less. The Zr content is preferably set to 0.15% or less. In order to more reliably obtain the above effects, the Zr content is preferably set to 0.001% or more, and more preferably set to 0.005% or more.

[0058] Ta: 0.05% or less Ta is an element that contributes to improving strength, and also contributes to improving corrosion resistance, although the mechanism is not necessarily clear, so it may be contained as necessary. However, Ta is an expensive element, and the inclusion of a large amount of Ta increases the steelmaking cost. Therefore, the Ta content is set to 0.05% or less. The Ta content is preferably 0.04% or less, more preferably 0.03% or less, and even more preferably 0.02% or less. In order to obtain the above effects more reliably, the Ta content is preferably 0.001% or more, and more preferably 0.005% or more.

[0059] B: 0.010% or less Since B is an element that improves hardenability and increases strength, it may be contained as necessary. However, even if B is contained in excess, the effect is saturated and the toughness of the base material and HAZ may decrease. Therefore, the B content is set to 0.010% or less. The B content is preferably 0.008% or less, more preferably 0.006% or less, and even more preferably 0.004% or less. In order to obtain the above effects more reliably, the B content is preferably 0.0003% or more, and more preferably 0.0005% or more.

[0060] In the chemical composition of the steel material of the present invention, one or more elements selected from Ca, Mg, Sr, Ba, and REM may be further contained within the ranges shown below for the purpose of deoxidization and inclusion control. Note that these elements are not necessarily essential in the steel material, so the lower limit of the content is 0%. The reasons for limiting each element will be explained.

[0061] Total of either or both of Ca and Mg: 0.010% or less Ca and Mg may be contained as necessary to form fine oxides. However, excessive addition of Ca and Mg leads to increased steelmaking costs. Therefore, the total content of Ca and Mg is set to 0.010% or less. Ca and Mg may be contained alone or both may be contained simultaneously. The total content of Ca and Mg is preferably 0.008% or less, and more preferably 0.005% or less. In order to more reliably obtain the above effects, the total content of Ca and Mg is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.

[0062] When either Ca or Mg is contained alone, the content of each of Ca and Mg is preferably 0.008% or less, more preferably 0.005% or less, and the content of each of Ca and Mg is preferably 0.0001% or more, more preferably 0.0003% or more.

[0063] Sr and / or Ba: 0.010% or less Sr and Ba may be contained as necessary to form fine oxides. However, excessive addition of Sr and Ba leads to increased steelmaking costs. Therefore, the total content of Sr and Ba is set to 0.010% or less. Sr and Ba may be contained either alone or both at the same time. The total content of Sr and Ba is preferably 0.008% or less, and more preferably 0.005% or less. In order to more reliably obtain the above effects, the total content of Sr and Ba is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.

[0064] When either Sr or Ba is contained alone, the Sr and Ba contents are each preferably 0.008% or less, more preferably 0.005% or less, and each preferably 0.0001% or more, more preferably 0.0003% or more.

[0065] REM: 0.010% or less REM (rare earth elements) are elements mainly used for deoxidation, and may be included as necessary to form fine oxides. However, excessive addition of REM leads to increased steelmaking costs. Therefore, the REM content is set to 0.010% or less. The REM content is preferably 0.005% or less, and more preferably 0.003% or less. In order to more reliably obtain the above effects, the REM content is preferably 0.0001% or more, more preferably 0.0003% or more, and even more preferably 0.0005% or more.

[0066] Here, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and the REM content means the total amount of the above elements. Note that lanthanoids are industrially added in the form of misch metals.

[0067] When one or more elements selected from Ca, Mg, Sr, Ba, and REM are contained, the total content is preferably 0.010% or less, or 0.008% or less, and is preferably 0.0003% or more, or 0.0005% or more.

[0068] (B) Oxide scale In the steel material according to the present invention, at least a part of the surface of the base material has an oxide scale, and the oxide scale has a concentrated area of ​​Cu and In. The presence of the concentrated areas of these elements provides a barrier effect against low-concentration sulfuric acid, thereby improving the corrosion resistance in a low-concentration sulfuric acid environment.

[0069] Here, the Cu and In concentrated portions refer to Cu and In that have diffused from the steel material and concentrated in the oxide scale.

[0070] The Cu and In enriched areas in the oxide scale are measured as follows. A line analysis is performed with an electron probe microanalyzer (EPMA) on a cross section perpendicular to the surface of the steel material and including the scale, and the enriched areas are defined as areas where the Cu and In contents are both at least twice as high as the contents in the base material. In the present invention, the conditions are as follows: acceleration voltage: 15 kV, beam diameter: up to 100 nm, irradiation time: 20 ms, and measurement pitch: 80 nm.

[0071] (C) Manufacturing method A method for producing a hot-rolled steel material according to one embodiment of the present invention will be described. The steel material according to this embodiment includes steel plates, steel pipes, etc., produced by hot rolling. The steel plate preferably has a thickness of 0.5 mm or more, more preferably 1.0 mm or more. When producing a steel material, the steel is melted in a conventional manner, the components are adjusted, and the resulting steel slab is cast, hot-rolled, and cooled to produce the steel material. The heating temperature of the steel slab is preferably 1080 to 1280°C.

[0072] <Descaling process> After the steel slab is heated, it is descaled at a water pressure of 12 MPa or more before hot rolling. There are two types of oxide scale: primary scale, which is formed during heating before hot rolling, and secondary scale, which is formed during hot rolling. By concentrating Cu and In in the secondary scale, it is possible to achieve a barrier effect against low-concentration sulfuric acid. If the primary scale remains on the steel surface during hot rolling, it becomes difficult for the secondary scale to form. Therefore, descaling is performed to remove the primary scale once before hot rolling. Also, if the water pressure for descaling is less than 12 MPa, the removal of the primary scale is insufficient. Therefore, the water pressure for descaling is set to 12 MPa or more.

[0073] <Hot rolling process> Next, 70% or more of the total reduction in the hot rolling process is performed between the heating temperature and 900°C. A secondary scale is likely to be formed between the heating temperature and 900°C. However, if rolling is performed with a large reduction amount, the secondary scale may peel off due to friction between the steel material and the rolling roll. However, a secondary scale is formed again between the heating temperature and 900°C. On the other hand, it is difficult to form a secondary scale again in a temperature range below 900°C. Therefore, the rolling ratio is increased in the temperature range from the heating temperature to 900°C where the secondary scale is likely to be formed. The rolling end temperature is preferably 800 to 870°C. In addition, when the rolling end temperature is 870°C or less, the rolling ratio in the temperature range from the heating temperature to 900°C is substantially 90% or less.

[0074] Here, the total rolling reduction is a value calculated by the following formula (iii) when the thickness of the steel slab before hot rolling is h1 and the thickness of the steel sheet after hot rolling is h2. (h1-h2) / h1×100 (iii)

[0075] Moreover, the rolling ratio in the temperature range from the heating temperature to 900°C is a value calculated by the following formula (iv) when the thickness of the steel sheet at 900°C is h3. (h1-h3) / (h1-h2)×100 (iv)

[0076] <Cooling process> After that, the average cooling rate from the rolling end temperature to 700°C is set to 10°C / min or more. The melting point of the compound of Cu and In is around 700°C. Therefore, if the material passes slowly through the temperature range from the rolling end temperature to 700°C, the molten Cu and In will diffuse from the oxide scale to the base material, and it will not be possible to form concentrated areas of Cu and In in the oxide scale. Therefore, by passing the material quickly through the temperature range from the rolling end temperature to 700°C, the compound of Cu and In can be kept in the scale.

[0077] After hot rolling, the steel sheet may be water-cooled or air-cooled and then reheated and quenched. After hot rolling, the steel sheet may be wound into a coil. After hot rolling, the steel sheet may be further heat-treated.

[0078] When manufacturing steel pipes, steel plates may be formed into a tubular shape and welded, and electric resistance welded steel pipes, forged welded steel pipes, spiral steel pipes, and the like can be produced.

[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0080] Steel having the chemical composition shown in Table 1 was melted and formed into a 17 kg ingot, which was then hot forged in a normal manner to produce a block with a thickness of 30 mm. The block was then hot rolled under the conditions shown in Table 2, and then allowed to cool to room temperature in air to produce a hot-rolled steel sheet. The total reduction rate and the rolling ratio from the heating temperature to 900°C were calculated based on the above-mentioned formulas (iii) and (iv), respectively.

[0081] [Table 1]

[0082] [Table 2]

[0083] <Presence or absence of enriched parts of Cu and In> The enriched parts of Cu and In in the oxide scale were measured as follows. Line analysis by EPMA was performed on a cross-section including the scale, perpendicular to the surface of the steel material, and a region where the contents of both Cu and In were more than twice as high as those in the base material were defined as the enriched parts. The measurement was carried out under the conditions of acceleration voltage: 15 kV, beam diameter: ~100 nm, irradiation time: 20 ms, and measurement pitch: 80 nm.

[0084] <Sulfuric acid resistance> From each steel plate, test pieces with a thickness equal to the thickness of the steel plate at the end of hot rolling shown in Table 2, a width of 25 mm, and a length of 25 mm were taken in two each, including the surfaces and the back surfaces with the oxide scale of the steel plate. Then, the end faces of the test pieces were finished by wet #600 polishing to obtain test pieces for corrosion resistance evaluation. For one of the two test pieces, a sulfuric acid immersion test was carried out by immersing it in a 50% sulfuric acid aqueous solution at 70 °C simulating a sulfuric acid dew point corrosion environment for 6 hours. For the remaining one test piece, a sulfuric acid immersion test was carried out by immersing it in 0.07% sulfuric acid at 40 °C simulating a weak acid sulfuric acid environment for 6 hours.

[0085] Thereafter, the corrosion rates were calculated from the corrosion weight loss of the test pieces by the sulfuric acid immersion test. In this example, when the corrosion rate by 50% sulfuric acid at 70 °C was 20.0 mg / cm 2 / h or less and the corrosion rate by 0.07% sulfuric acid at 40 °C was 1.0 mg / cm 2 / h or less, it was judged to have excellent sulfuric acid resistance.

[0086] <Hot workability> The surface of the hot-rolled material rolled under the above conditions was visually inspected, and those with cracks were marked as ×, and those without cracks were marked as 〇 to evaluate the hot workability.

[0087] The results of the sulfuric acid immersion test and the hot workability evaluation are summarized in Table 3. Note that "-" in Table 3 means that test pieces could not be collected due to deterioration of hot workability, and sulfuric acid resistance could not be evaluated. Also, in Table 3, "Corrosion rate (condition 1)" shows the corrosion rate with 50% sulfuric acid at 70°C, and "Corrosion rate (condition 2)" shows the corrosion rate with 0.07% sulfuric acid at 40°C.

[0088] [Table 3]

[0089] As shown in Table 3, Test Nos. 1 to 28, which satisfied all the provisions of the present invention, were excellent in both sulfuric acid resistance and hot workability. In contrast, Test Nos. 29 to 34, which are comparative examples, were inferior in sulfuric acid resistance or hot workability. [Industrial Applicability]

[0090] The steel material of the present invention can be used in smoke exhaust systems for boilers that burn fossil fuels such as heavy oil and coal, gas fuels such as liquefied natural gas, general waste such as urban waste, industrial waste such as waste oil, plastics, and exhaust tires, and sewage sludge, etc. Specifically, it can be suitably used for flue ducts, casings, and heat exchangers of smoke exhaust systems, gas-gas heaters consisting of two heat exchangers (a heat recovery unit and a reheater), desulfurization equipment, electric dust collectors, induced draft fans, basket materials and heat transfer element plates of rotary regenerative air preheaters, etc.

Claims

1. A hot-rolled steel material having an oxide scale on at least a portion of a surface of a base material, The chemical composition of the base material is, in mass%, C: 0.01 to 0.10%, Si: 0.04-0.40%, Mn: 0.50 to 1.50%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Ni: 0.02-0.30%, In: 0.005 to 0.020%, Al: 0.005-0.05%, The sum of one or both of Mo and W: 0.01 to 0.30%, P: 0.015% or less, S: 0.015% or less, N: 0.005% or less, O: 0.0035% or less, The balance is Fe and impurities. The following formulas (i) and (ii) are satisfied: The oxide scale has a Cu and In enriched portion. Hot rolled steel. 10.0≦Cu / In...(i) 2.6≦(Cu / 64) / ((Sb / 122)+(In / 115))≦5.5...(ii) In the above formula, the element symbols represent the content (mass%) of each element contained in the hot-rolled steel material.

2. A hot-rolled steel material having an oxide scale on at least a portion of a surface of a base material, The chemical composition of the base material is, in mass%, C: 0.01 to 0.10%, Si: 0.04-0.40%, Mn: 0.50 to 1.50%, Cu: 0.10-0.50%, Sb: 0.01 to 0.30%, Ni: 0.02-0.30%, In: 0.005 to 0.020%, Al: 0.005-0.05%, The sum of one or both of Mo and W: 0.01 to 0.30%, P: 0.015% or less, S: 0.015% or less, N: 0.005% or less, O: 0.0035% or less, and further containing one or more selected from the group consisting of the following groups A, B, and C: The balance is Fe and impurities. The following formulas (i) and (ii) are satisfied: The oxide scale has a Cu and In enriched portion. Hot rolled steel. 10.0≦Cu / In...(i) 2.6≦(Cu / 64) / ((Sb / 122)+(In / 115))≦5.5...(ii) In the above formula, the element symbols represent the content (mass%) of each element contained in the hot-rolled steel material. [Group A] One or more selected from the group consisting of As: 0.10% or less, Bi: 0.10% or less, Se: 0.10% or less, Te: 0.10% or less, Pb: 0.10% or less, Zn: 0.10% or less, Ga: 0.10% or less, Ge: 0.10% or less, Co: 0.30% or less, and Hf: 0.30% or less. [Group B] One or more selected from the group consisting of Cr: 1.0% or less, Nb: 0.10% or less, V: 0.10% or less, Ti: 0.20% or less, Zr: 0.20% or less, Ta: 0.05% or less, and B: 0.010% or less [Group C] One or more selected from the group consisting of Ca and Mg, one or both of which in total are 0.010% or less, Sr and Ba, one or both of which in total are 0.010% or less, and REM, which are 0.010% or less.

3. The hot-rolled steel material according to claim 2, wherein the chemical composition of the base material contains one or more elements selected from the group A.

4. The hot-rolled steel material according to claim 2, wherein the chemical composition of the base metal contains one or more elements selected from the B group.

5. The hot-rolled steel material according to claim 2, wherein the chemical composition of the base metal contains one or more elements selected from the C group.

Citation Information

Patent Citations

  • High workability and good weldability sulfuric acid dew point corrosion resistant steel sheet

    JP2001164335A

  • Low alloy steel having excellent hydrochloric acid- corrosion and sulfuric acid-corrosion resistance and welded joint thereof

    JP2003213367A

  • Acid corrosion resistant steel

    JP2007239094A

  • Acid dew-point corrosion resistant steel and exhausted gas flow path structure member

    JP2012057221A

  • Hot-rolled steel

    WO2021095185A1